Blood Pressure and Global Risk Assessment in a Swedish Population - Jenny Eckner; Charlotte A. Larsson; Lennart Råstam; Ulf Lindblad (International Journal of Hypertension)
This study investigated the association between SCORE and the 2007 ESH-ESC blood pressure categories and explored achievements of blood pressure goals considering global risk. In 2001–2005, a random sample of inhabitants aged 30–74 years in southwestern Sweden was invited to a survey of cardiovascular risk factors. The study enrolled 2816 participants (participation rate 76%). Blood pressure was categorized according to the 2007 ESH-ESC guidelines. Global risk of 10-year CVD death was estimated using the Swedish SCORE chart also accounting for additional risk from diabetes (SCORE-DM). SCORE-DM increased in both sexes from optimal blood pressure to manifest hypertension but did not differ between the normal blood pressure categories. However, SCORE-DM became significantly higher among those with temporarily high blood pressure (men 3.3 SD (1.7), women 1.1 (1.8)) and hypertension (3.6 (2.0), 2.0 (2.0)), compared to optimal blood pressure (1.6 (2.9), 0.6 (1.9)). In the presence of both hypertension and diabetes, high-risk subjects dominated (men 76%, women 61%), and correspondingly a major proportion of patients with known hypertension were at high risk at a blood pressure ≥160/100 mm Hg. These findings have strong implications on blood pressure evaluation in clinical practice and support the use of SCORE to evaluate global risk.